Analisis Hukum Terhadap Pemutusan Hubungan Kerja Di PT. Freeport Indonesia : Tinjauan Atas Putusan dan Kepatuhan Terhadap Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan - Anwar, Muhamad Saeful; Aliza, Mutiara Nur; Satria, Fazar; Salsabila, Dwi Intan Putri Hanum; Daimonica, Shine (Journal of Industrial Relations Studies, 2025)
This research aims to find out and provide an explanation regarding whether the panel of judges' decision reflects PT Freeport Indonesia's compliance with Law Number 13 of 2003 concerning Employment as well as knowing and providing an explanation of the legal basis used by the panel of judges in deciding the case. In this context, the author uses a normative legal approach which refers to Law Number 13 of 2003 concerning Employment as the main legal basis. This research also examines the processes and procedures implemented by companies in terminating employment relationships as well as the protection provided to affected employees. The research results show that there is a clear legal basis, the implementation of protection for workers in cases of Termination of Employment still faces challenges, especially related to difficulties in accessing legal mechanisms. This research concludes that the decision of the panel of judges in this case reflects that PT Freeport Indonesia has complied with Law Number 13 of 2003 concerning employment, especially in terms of termination of employment relations and the panel of judges in this case has correctly referred to the legal basis regulated by termination work relationship. In this case, the termination of employment taken by PT Freeport Indonesia is in accordance with the procedures regulated by law, including the provision of workers' rights such as severance pay